Impacts of chemical dispersants on oil-degrading microorganisms - Rughöft, Saskia (Universität Tübingen, 2023)
Accidental crude oil spills can cause substantial environmental damage in marine ecosystems. During the emergency spill response, chemical dispersants (= solvent-surfactant mixtures) are often applied with the aim of reducing ecological and economic damage due to floating and beached oil. However, the use of chemical dispersants remains controversial due to their inherent toxicity potential and uncertainties about their ecological effects, including their influence on affected seawater microbial communities and native oil/hydrocarbon-degrading microorganisms. The scientific literature on this topic is characterized by contradictory findings and a lack of data on the underlying mechanisms of observed dispersant effects on oil-degrading bacteria. Therefore, this work aimed to determine and elucidate the impacts of chemical dispersants on oil-degrading microorganisms by examining their effects on different ecological levels. First, the response of environmental seawater microbial communities from the Arctic Ocean and the North Sea to chemical dispersant exposure was determined by performing laboratory seawater microcosm experiments that simulated oil spill conditions and monitored oil biodegradation potential, as well as microbial community dynamics. These studies showed that while biodegradation of several aliphatic and aromatic hydrocarbons was not substantially affected by chemical dispersant addition, lower cell numbers and the enrichment of a distinct community of hydrocarbon- and/or dispersant-degrading bacterial taxa were observed. Additionally, persistent organic compounds (likely dispersant-derived) were observed in dispersant-amended microcosms and the application of inorganic nutrients (i.e. biostimulation) was identified as a promising alternative approach to dispersant application in potential future Arctic Ocean oil spills. Next, the model organism Marinobacter sp. TT1 was investigated in order to identify the effects of chemical dispersant exposure on growth, alkane biodegradation activity and ...